1999
DOI: 10.1038/sj.bjc.6690596
|View full text |Cite
|
Sign up to set email alerts
|

The effect of psychological interventions on anxiety and depression in cancer patients: results of two meta-analyses

Abstract: Between 15 and 40% of cancer patients develop clinical anxiety and/or depression (Derogatis et al, 1983;Massie and Holland, 1990;Parle et al, 1996). Even for those ostensibly cured the prevalence remains appreciably higher than that of the general population a year or more after diagnosis (Devlen et al, 1987). This evidence, combined with significant pressure from service users, has led to increasing provision of psychological interventions in British oncology services. This has been piecemeal (Fallowfield, 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
332
6
25

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 473 publications
(390 citation statements)
references
References 54 publications
27
332
6
25
Order By: Relevance
“…Interventions designed to enhance well-being among cancer patients are supported by research showing that moderate to high levels of stress are commonly experienced by individuals attempting to cope with the disease and its consequences (e.g., Sellick & Crooks, 1999;Sheard & Maguire, 1999). In this study, patients were enrolled in an 8-week MBSR program.…”
Section: Study 5 Effects Of Mindfulness On Well-being In a Clinical mentioning
confidence: 99%
“…Interventions designed to enhance well-being among cancer patients are supported by research showing that moderate to high levels of stress are commonly experienced by individuals attempting to cope with the disease and its consequences (e.g., Sellick & Crooks, 1999;Sheard & Maguire, 1999). In this study, patients were enrolled in an 8-week MBSR program.…”
Section: Study 5 Effects Of Mindfulness On Well-being In a Clinical mentioning
confidence: 99%
“…28,36 Comparisons among effect sizes are difficult to make because of the diversity of interventions and study designs. Nevertheless, a major strength of the current study was that the three target symptoms were combined into a single composite outcome (consisting of the vector of the means on the scores of breathlessness, fatigue and anxiety).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with high scores still require proper clinical assessment; if the clinician lacks either the necessary interviewing skills, or the inclination to probe further, they can at least refer distressed patients on for more specialist help on an informed basis. Furthermore there is evidence for improved efficacy of psychological interventions in screened populations (Sheard and Maguire, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…If psychological problems are recognized by healthcare professionals then patients can be referred on for appropriate and effective interventions (Fallowfield, 1995). Given the extent of psychiatric morbidity and the proven efficacy of many different types of intervention for adult cancer patients (Meyer and Mark, 1995;Sheard and Maguire, 1999) this should form an important part of effective clinical management. Unfortunately several studies have shown that oncologists are not especially skilled at either discussing psychological problems in general, or at recognizing anxiety or depression (Hardman et al, 1989;Ford et al, 1994;Newell et al, 1998;Passik et al, 1998).…”
mentioning
confidence: 99%